Impact of Perceived Product Value on Customer-Based Brand Equity: Marx’s Theory – Value-Based Perspective - Qiao, Yonggang; Yin, Xirui; Xing, Gao (Frontiers in Psychology, 2022)
Management research is allocating energies to seek ways to improve organizational performance. Branding has become a significant phenomenon that academicians and scholars have studied. Improving the brand’s overall equity requires strategies that the brand managers must implement. Based on Marx’s theory, the present study attempts to determine the role of product perceived value on customer-based brand equity, brand resonance and customer affective commitment, respectively. Moreover, this study also tries to determine the mediating roles of brand resonance and customer affective commitment in the relationship between product perceived value and customer-based brand equity, respectively. For this purpose, the data were gathered from 310 customers of branding products in China. The present study applied partial least square structural equation modeling for empirical analyses using Smart PLS software. The present study’s findings acknowledge that product perceived value did not directly influence customer-based brand equity. However, results confirmed that product perceived value positively influences brand resonance and customer affective commitment. Furthermore, the outcomes of the present study also concluded that both brand resonance and affective commitment played a mediating role between product perceived value and customer-based brand equity, respectively. Theoretically, the study contributed to the literature by examining the influence of product perceived value on customer-based brand equity. The study also enriched the literature by providing key findings related to the mediating roles of brand resonance and customer affective commitment. Practically, the study is beneficial for the brands and they can enhance product perceived value by improving product design, effectively communicating product benefits, and executing effective promotional strategies.